Production of syngas via dry reforming of methane with carbon dioxide over dolomite supported cobalt-based catalyst - Anuar, Arfaezah (2018)
Dry reforming of methane with carbon dioxide (DRM) has received great attention from researchers as this reaction is utilizing two main greenhouse gases which are CH4 and CO2 gases in producing valuable syngas. In addition, H2/CO ratio produced in this reaction is equivalent to 1. Due to this, the syngas produced is compatible with various chemical and liquid fuel syntheses. However, the formation of carbon on the surface of the catalysts hinders the active sites to take part in the reaction is the main drawback in DRM reaction. The main objective of this study is to develop cobalt based catalysts with dolomite as support by impregnation method with different types of non-noble metals such as Ce, Ni and La. A series of monometallic catalysts (Co-based) at different metal loadings, 5 wt% - 25 wt%, were prepared in order to determine the optimum loading of Co. Meanwhile, for bimetallic catalysts, Co with other metal with wt% ratio of 20:10 was impregnated on dolomite to form Co-La/Dol, Co-Ce/Dol and Co-Ni/Dol catalyst. The synthesized catalysts were characterized by various methods including X-ray diffraction (XRD), H2-temperature programmed reduction (H2-TPR), CO2-temperature programmed desorption (CO2-TPD), Field emission scanning electron microscope with energy dispersive X-ray spectrometer (FESEM-EDX), thermal gravimetric analysis (TGA) and N2 adsorption-desorption to determine their physico-chemical properties of the prepared catalysts as well as the carbon formation on the used catalysts. The catalytic evaluation showed that both monometallic and bimetallic catalysts gave high (> 90%) conversion of CH4 and CO2 at 900 oC without in-situ reduction with 5% H2 gas. However, as the temperature goes down to 850 – 750 oC, the unreduced Co/Dol catalyst gave poor catalytic performance with conversion around 59%-20%. The monometallic catalyst was reduced prior to reaction in order to obtain high conversion of CH4, 35% - 94% at 750 – 850 oC. Meanwhile, for unreduced bimetallic catalysts, only Co-Ni/Dol catalyst gave high activity, with conversion of 80% for both feed gases at 800 oC, whilst other bimetallic catalysts have to be reduced prior to the reaction to obtain high conversion of CH4 and CO2 gas. Among these catalysts, Co-Ni/Dol catalyst exhibited the highest catalytic performance either reduced of unreduced. In addition, it showed good thermal stability for 72 h at lower temperature, 750 oC with conversion of 91% and 92% for CH4 and CO2 gas, respectively with CO2:CH4 at 1:1 ratio.